ELIMINASI PENGARUH GAYA GONCANG TERHADAP KEAUSAN BANTALAN BOLA RADIAL - Galbi, Mohammad; A, Ishak (Bina Teknika, 2015)
The vibration caused by the engine rotation must be within specified limits. A mechanism that is unbalanced or unstable will lead to excessive wear on ball bearings. Unbalanced condition is one of them due to a shaking force on the crankshaft which affects the wear of ball bearings as a pedestal. The problems that have been faced is the replacement of bearings after a failure caused by excessive force due to imbalance rocking rounds to get a replacement bearings before reaching failure (unreliable). The purpose of this study was to determine reliably the age of radial ball bearings in order to maintain the performance of the motor as well as the prevention of unplanned downtime nature. Prevention "malfunction" will avoid the effects on other components of diesel engines, particularly against compression disorders. Variation of residual unbalanced force large enough to cause interference with the ball bearings to reduce Mo, the rest of the unbalanced force can be siginifkan diturnkan.